Hybrid Learning in New Normal Times: Shedding Light on the Current Teaching Practices Towards Second Language Acquisition in Higher Education Context - Hudriati, Andi; Yunus, Muhammad; Arham, Muhammad (International Journal of Language Education, 2023)
With the pandemics still an ongoing issue and the sudden shift to full distance learning, English language learning in Indonesia has been severely impacted. The current study sheds light on the current teaching practices within Academic writing Classes of Full-time online learning in Indonesian Higher Education Context during the pandemics. The aim of the study focuses on (1) the impact of the change in learning process during the pandemics in terms of EFL students’ second language acquisition within academic writing environment and (2) lecturers’ perception on the shift in the approaches they used to accommodate safety protocols during the pandemics (3) how lecturers cope with the technological changes made to provide a successful SLA input in a hybrid learning setting. This study was carried out through a qualitative approach with a case study design in mind. The study analyzed the current teaching process based on Westhoff’s effective second language acquisition which served as the framework of the study. The study employed a qualitative approach using observation and interview as the instrument and analyzed based on Miles & Huberman’s qualitative data analysis technique. The present study found that there were three approaches that the lecturers preferred, they are (1) Hybrid-led second language Acquisition, (2) Synchronous-led second language acquisition, and (3) Asynchronous-led second language acquisition. These approaches were influenced by the lecturers’ views which was categorized into three namely; (1) hybrid-led which focuses both on theoretical and practical, (2) theoretical-led which leans solely on writing and reading skills, and (3) practical-led which emphasized on oral output production. The study presents a finding on how Indonesian lecturers current teaching practices during the pandemics within academic writing setting by looking into the teaching performance and how their views shape the learning process for students to learn the target language.